The London Stage 1910-1919: A Calendar of Productions, Performers, and Personnel - Wearing, J. P. (Rowman & Littlefield Publishers, 2013)
Theatre in London has celebrated a rich and influential history, and in 1976 the first volume of J. P. Wearing’s reference series provided researchers with an indispensable resource of these productions. In the decades since the original calendars were produced, several research aids have become available, notably various reference works and the digitization of relevant newspapers and periodicals. This second edition of The London Stage 1910–1919: A Calendar of Productions, Performers, and Personnel provides a chronological calendar of London shows from January 1910 through December 1919. The volume chronicles more than 3,000 productions at 35 major central London theatres during this period. For each entry the following information is provided: Title Author Theatre Performers Personnel Opening and closing dates Number of performances Other details include genre of the production, number of acts, and a list of reviews. A comment section includes other interesting information, such as a plot description, first-night audience reception, noteworthy performances, staging elements, and details of performances in New York either prior to or after the London production. Among the plays staged in London during this decade were Chu Chin Chow, The Gaol Gate, Hindle Wakes, Justice, Kismet, Pygmalion, and Rebecca of Sunnybrook Farm, as well as numerous musical comedies (British and American), foreign works, operas, and revivals of English classics. A definitive resource, this edition revises, corrects, and expands the original calendar. In addition, approximately 20 percent of the material—in particular, information on adaptations and translations, plot sources, and comments—is new. Arranged chronologically, the shows are fully indexed by title, genre, and theatre. A general index includes numerous subject entries on such topics as acting, audiences, censorship, costumes, managers, performers, prompters, staging, and ticket prices. The London Stage 1910–1919 will be of value to scholars, theatrical personnel, librarians, writers, journalists, and historians.